Nature of the asymmetry in the hydrogen-bond networks of hexagonal ice and liquid water - Kühne, Thomas D.; Khaliullin, Rustam Z. (Journal of the American Chemical Society, 2014)
The interpretation of the X-ray spectra of water as evidence for its asymmetric structure has challenged the traditional nearly tetrahedral model and initiated an intense debate about the order and symmetry of the hydrogen-bond network in water. Here, we present new insights into the nature of local interactions in ice and liquid water obtained using a first-principle energy decomposition method. A comparative analysis shows that the majority of molecules in liquid water in our simulation exhibit hydrogen-bonding energy patterns similar to those in ice and retain the four-fold coordination with only moderately distorted tetrahedral configurations. Although this result indicates that the traditional description of liquid water is fundamentally correct, our study also demonstrates that for a significant fraction of molecules the hydrogen-bonding environments are highly asymmetric with extremely weak and distorted bonds. © 2014 American Chemical Society.
CRIS-Team Scopus Importer:2023-03-20